Tolkningspraktiker och bedömningskulturer : Om bedömning inom högre musikutbildning – en metaanalys av några delprojekt - Olsson, Bengt; Nielsen, Einar (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2020)
Practices of interpretation and cultures of assessment – a meta-analysis of some assessment projects Research on assessment of musical performances is quite comprehensive but a major part embraces projects within schools on the primary, secondary and tertiary level. There is a lack of studies on assessments within higher music education, studies focusing on criteria, norms and values among teachers and tutors. Generally, these public assessments seem to be considered subjective and random and not knowledge-based. In this meta-study three projects are analysed and the results show, on the contrary, that assessment of performances rests on values that are deeply integrated in the context and the competence of the assessors of higher music education. In the first project, a pilot study, the results showed three dominating criteria being used by five professors: technical and analytical skills; performance and style or genre knowledge; and personal musical expression and communication. These three criteria have a triangular relationship and this leads to two original assessment models. The first model embraces an “integrated model”, i.e., the tensions between the three positions are diminished and they are very difficult to perceive individually. The quality of musical experience of this artistic model is also the most highly ranked assessment. The other model is a divided version in which one or more of the criteria were perceived. The assessors considered this to be a lack of quality. The musicians needed to improve their skills and knowledge to perform on a professional level and to be higher ranked. In the second project, fifteen professors within four Danish and Swedish universities were interviewed. Here, the individual tutors supported the hypothetical models of the pilot study. Moreover, they introduced a more advanced discourse of the structure of the criteria, in that they introduced a distinction between analytical and fuzzy criteria and, further, discussed the differences between concept-based, divided perspectives and integrated, holistic approaches. The connections between the two levels, divided, analytical criteria, and integrated, fuzzy criteria, respectively, are obvious, although the levels are clearly separated. This shows four prominent themes among the results as well. These concern ‘the aesthetic dimensions of the performance’, ‘the musicians’ presence on stage during the performance’, ‘interpretation as a way of understanding’, and ‘the importance of self-government in relation to the musical style performed by the musician’. In the final analysis of the same empirical material (the third project), all results are summarised into a tentative theory of musical assessments. The theory is based on three major dimensions. The first dimension concerns the criteria triangle and the discussion on its structure and functions, and, in addition, how the assessments are linked to the two basic models. In the second part of the dimension a distinction in the triangle based on four different themes, presented above, is further developed. This gives, for example, space for subjectivity in the assessments. The second dimension is connected to the assessor’s competence. This means that questions of ‘who’ is assessor and how well he/she is acquainted with a certain genre or a repertoire are important. In the final dimension, the importance of the assessments’ context is discussed. Institutional norms and values play an important role in deciding whether a performance is good or bad. What is shown in all projects discussed here is that these contexts, which belong to departments and academies within higher music education, are of crucial importance. To conclude, the three dimensions may be described as a continuum, with its starting-point in a concept-based triangle with clearly defined analytical criteria, and with its endpoint in contextual norms closely linked to fuzzy criteria including artistic values and communication. Although all three dimensions are connected with each other, and this is reflected in all studies, we also found a lack of balance between them. The artistic dimensions have the greatest importance due to contextual traditions and the assessors’ professional musical experiences.